Education of High Wisdom Intelligence- - Ma, Wen; Zhu, Yanqin; Li, Chunli; Zhang, Bo; Tian, Xin (Advances in Social Sciences Research Journal, 2021)
Education of high wisdom intelligence lays the foundation for social education, school education, family education and self-education. It ensures all the educational contents that social education, school education, family education and self-education deliver; for instance, cognitive education, mindful education and practical education. The number of talented persons who are equipped with high wisdom intelligence will immediately determine the quality of humankind’s entire life, and the future trend for humankind’s innovation and creation in fields such as thinking, cognition, society, politics, economy, military, science, arts, culture, and so on. In this paper, I will discuss issues of family education, school education, social education, and self- education ; and how these four education with high wisdom intelligence contribute to the cultivation of talents with high wisdom intelligence.